(untitled) (Eurasian Journal of Engineering and Technology, 2024)
The article deals with the development of information and methodological support for the decision-making process in the formation of the assortment, industrial clothing. The structure of the information retrieval process at the initial stages of design is proposed, which provides a search for options for graphic solutions for special clothing based on the identification of optimal zones of contamination and wear of clothing in accordance with real operating conditions. A database of graphic diagrams of various design and technological solutions has been developed, which allow expanding the functional modules of automated systems. The use of a graphic base for displaying a collection of industrial clothing in computer-aided design significantly reduces design development time and reduces the number of errors caused by the human factor.